2014
DOI: 10.2147/itt.s49656
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-based immunotherapy for autoimmune disease: current status

Abstract: Autoimmune diseases are common chronic disorders that not only have a major impact on the quality of life but are also potentially life-threatening. Treatment modalities that are currently favored have conferred significant clinical benefits, but they may have considerable side effects. An optimal treatment strategy for autoimmune disease would specifically target disease-associated antigens and limit systemic side effects. Similar to allergen-specific immunotherapy for allergic rhinitis, antigen-specific immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…It has been demonstrated that peptides used in combination can be more effective than individual sequences in preventing or reversing allo- or auto-antibody production. 32,34,42,43 Peptides 2 (aa6-20) and 82 (aa711-725) were selected to be tested in combination here, since epitopes they contain were previously identified as the most immunodominant, 7 capable of eliciting Th responses in 65% of ITP patients tested, and they had also each demonstrated some, albeit variable, inhibition of antibody generation in the individual peptide experiments. It was determined whether prior treatment with an equimolar mixture of peptides 2 (aa6-20) and 82 (aa711-725) prevented induction of the antibody response to immunization with purified GPIIb/IIIa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that peptides used in combination can be more effective than individual sequences in preventing or reversing allo- or auto-antibody production. 32,34,42,43 Peptides 2 (aa6-20) and 82 (aa711-725) were selected to be tested in combination here, since epitopes they contain were previously identified as the most immunodominant, 7 capable of eliciting Th responses in 65% of ITP patients tested, and they had also each demonstrated some, albeit variable, inhibition of antibody generation in the individual peptide experiments. It was determined whether prior treatment with an equimolar mixture of peptides 2 (aa6-20) and 82 (aa711-725) prevented induction of the antibody response to immunization with purified GPIIb/IIIa.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 In contrast to previous untargeted approaches, antigen-specific immunotherapy offers the prospect of rebalancing pathogenic CD4 + Th and Treg responses, without compromising the rest of the immune system. 2832 Precedents in models of other immune-mediated diseases demonstrate that this can be achieved by appropriate administration of short, synthetic peptides containing CD4 + T-cell epitopes from the respective target antigens, with peptide products being tested in clinical trials for the treatment of a number of conditions, including type I diabetes, multiple sclerosis and rheumatoid arthritis. 2832 The approach induces immune regulation, which, in addition to suppressing inflammatory T-cell responses, also has the potential to inhibit helper-dependent antibody production, as demonstrated by the success of peptide therapy in blocking IgG responses to the RhD blood group protein in a humanized murine model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a few promising results of early phases clinical trials in humans, the use of AIT for autoimmune diseases has not yet been brought into practice ( 13 ). This could be partially explained by the fact that by the time an autoimmune disease is diagnosed, tissue damage may have already occurred or become irreversible, as in the case of type I diabetes.…”
Section: Antigen-based Immunotherapy and Its Application In Autoimmunmentioning
confidence: 99%
“…and RA as well as phase I studies in humans [213]. Finally, tDCs can be used as a new therapeutic strategy to reestablish immune tolerance or to prevent ADs [209,214].…”
Section: Immune Tolerance Induction As a Therapy For Autoimmune Diseasesmentioning
confidence: 99%